The long-term general practice healthcare of women with a history of gestational diabetes: A Scoping Review Protocol [version 2; peer review: 2 approved] - James O'Flynn; Rita Forde; Rita McMorrow; Sheena McHugh; Aisling A. Jennings; Christine Newman; Tony Foley (HRB Open Research)
Introduction Gestational Diabetes Mellitus (GDM) is a hyperglycaemic condition diagnosed during pregnancy. GDM is strongly associated with future development of type 2 diabetes and cardiovascular disease. Lifestyle and pharmacological interventions can reduce the risk of developing type 2 diabetes. General practice is the recommended setting for long-term follow-up of women with a history of GDM. However, rates of follow-up are suboptimal. The evidence around long-term general practice healthcare for women with a history of GDM has not previously been reviewed. Aims The aim of this scoping review is to explore the current evidence base for the long-term care of women with a history of GDM in general practice. Study Design The study described by this protocol is a scoping review. The study design was informed by Joanna Briggs Institute methodology. Methods Empirical qualitative and quantitative research studies published since 2014 will be identified from a search of the following databases: MEDLINE (Ovid), EMBASE (Elsevier), CINAHL, PsycINFO, Academic Search Complete and SocIndex. The review will identify key characteristics of the literature. Framework analysis will be used to map the findings against the Chronic Care Model, a primary care-based framework that sets out the core components for optimal long-term healthcare. Results A numerical descriptive summary (using frequencies) will describe the overall extent of literature, and the range and distribution of its component parts, including the geographical and economic settings, research methods, interventions, outcomes and findings. The qualitative analysis will map interventions and descriptions of care to components of the chronic care model. Research gaps will be reported, and research needs and priorities will be suggested. Conclusion The findings of this scoping review will have the potential to inform future research efforts in the area. Registration This protocol has been registered in Open Science Framework (https://osf.io/bz2vh).